High-Detailed evaluation of the right atrial anatomy by three-dimensional rotational angiography during ablation procedures for atrioventricular nodal reentrant tachycardia and atrial flutter. (3rd September 2018) - Garweg, Christophe; De Buck, Stijn; Vandenberk, Bert; Willems, Rik; Ector, Joris
Abstract: Aim. 3D Rotational angiography (3DRA) allows for detailed reconstruction of atrial anatomy and is often used to facilitate pulmonary vein isolation. This study aimed to reappraise the anatomy of the right atrium (RA) using 3DRA, specifically looking at Koch's triangle and the cavotricuspid isthmus (CTI) in atrio-ventricular reentrant tachycardia (AVNRT) and atrial flutter (AFl) ablation. Methods and results. 3DRA was performed in 97 patients: AVNRT = 51 and AFl = 46. Dimensions of Koch's triangle and CTI were highly variable between individuals but were not different in both ablation groups. RA volume was significantly larger in AFl patients ( p = .004) while indexed RA volume to the body surface area (RAVI) was lightly different ( p = .024). In univariate Cox analysis, age ( p = .003), RAVI ( p < .001) and previous ablation of AFl ( p = .003) were predictors of AF occurrence . In multivariate Cox analysis, RAVI was the only independent predictor of AF occurrence. RAVI >80 ml/m 2 was a strong predictor for AF during follow-up. Conclusion. 3DRA allows for detailed per-procedural evaluation of RA anatomy and revealed a great variability in Koch's triangle and CTI dimensions and morphology. RA enlargement as measured by RAVI was an independent predictor for AF occurrence during follow-up.